Power Flow Optimizaiton Control in AC / DC Hybrid Distribution Network Based on Power Ｒouter - YIN Zhan; DU Ｒen-ping; JIANG Li-ming; ZHANG Jian-wen; SHI Gang; ZHOU Jian-qiao; ZHU Cheng-hao (Journal of Harbin University of Science and Technology)
In recent years，a large number of distributed new energy power generation devices have been integrated into the grid，resulting in bidirectional power flow in distribution network. At the same time，traditional end users have also begun to join the distribution network as power supplies，which cannot be afforded by traditional distribution network systems. Therefore，it is necessary to transform and optimize the traditional grid structure to meet the higher standard of electricity demand in the future economic society. This paper explores a new type of AC /DC hybrid distribution network networking structure，that is，through the power router to achieve medium voltage DC interconnection between different distribution areas，forming a layer of network DC energy，optimizating the entire distribution by the DC power flow. This paper firstly introduces the new distribution network structure， and then uses the AC-DC hybrid power flow calculation as a tool to carry out the distribution network operation simulation. Finally，based on the particle swarm optimization algorithm，the new distribution network structure is optimizedly controlled. Through the analysis of the simulation results，it is found that the new distribution network structure adopted in this paper has a large optimization effect on the network loss and node voltage status of the distribution network.